Efficiency level on civil registry petition process of Philippine statistics authority: towards operation digitalization system - Oribia, Ramil B. (b)
The Philippine Statistics Authority (PSA) faces challenges in managing civil registration petitions due to its manual method, which is time-consuming and error-prone. It needs more agility to meet the needs of a rapidly growing population, especially in the digital age. The PSA is implementing a digitalization system to streamline operations and improve accuracy. The research aims to assess the current efficiency levels in the civil registry petition procedure and identify areas for improvement. Adopting a digital operations system could lead to faster processing times, better data management, and increased stakeholder accessibility. The research will use qualitative and quantitative methods to understand digitization's challenges and future benefits in civil registry petition processes. Interviews, surveys, and focus groups will be conducted with key stakeholders to identify effective strategies and potential traps. This study aims to provide insights for the PSA in developing a digitization system for civil registries, advancing digital transformation in the public sector, and laying the groundwork for future research. Finally, this study aimed to investigate the effectiveness of the Philippine Statistics Authority's civil registry petition procedure and consider the advantages of converting to a digital operating system. By identifying present problems and analyzing the benefits of digitalization, this research offered helpful guidance to the PSA to streamline operations, improve service delivery, and meet the increasing requirements of its stakeholders and Filipino residents.
Master Thesis
Keywords: Philippine Statistics Authority; Digitalization System; Electronic transformation; Philippine Civil Registry